Pragmatic and communicative specifics of intolerant Internet discourse, determined by the semantics of wealth (based on the German language) - Palahina, Alina M. (Journal of the Belarusian State University. Philology, 2026)
This article presents a nomenclature of communicative strategies and speech tactics of intolerant discourse that are actualised within the computer-mediated communication. The factual material of the study are German-language online comments, published on the videohosting YouTube from 1 January 2023 to 31 December 2024, and containing verbalisation of hostility conditioned by the wealth semantics. The aim of the study is to establish the specifics of the pragmatic and communicative organisation of intolerant online discourse in German, conditioned by the semantics of material wealth. The study found the most common speech tactics of hate speech towards the named group in the German-language personal online-discourse. The results obtained are valuable in identifying the characteristics of hostility verbalisation toward a social group identified not by an innate, but by an acquired characteristic. Practical application of these findings is possible in the context of linguodidactics, linguistic expertise, and at all levels of the educational process, as well as for ensuring public information security and constructive, tolerant interactions online.
Keywords: intolerant discourse; Internet discourse; communicative strategy; speech tactics; wealth; hate speech